2011
DOI: 10.1038/pj.2011.113
|View full text |Cite
|
Sign up to set email alerts
|

Helix–coil transformation of poly(γ-benzyl-L-glutamate) with polystyrene attached to the N or C terminus in trifluoroacetic acid–chloroform mixtures

Abstract: The helix-coil transformations of block copolymers composed of poly(c-benzyl-L-glutamate) (PBLG) and polystyrene (PS), in which PS was attached to either the N terminus (PBLG n -N-PS m ) or the C terminus (PS n -C-PBLG m ) of PBLG, were investigated in trifluoroacetic acid (TFA)-chloroform mixtures with TFA concentrations in the range of 0.7-10 vol%. The helical content (f H ) estimated from 1 H nuclear magnetic resonance measurements indicated that the PBLG segment in PBLG 55 -N-PS 160 underwent a gradual hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…A x-amino-functionalized PS macroinitiator (M n = 2100, M w / M n = 1.15) was synthesized by atom transfer radical polymerization of styrene followed by Gabriel method as described in a previous paper [27]. A mixture of N-carboxy-c-benzyl-L-glutamate anhydride (3.00 g, 11.4 mmol), the PS macroinitiator (200 mg, 0.09 mmol), and dry chloroform (150 ml) was placed in a flask and stirred for 3 days.…”
Section: Synthesis Of Ps-b-poly(l-glu)mentioning
confidence: 99%
See 1 more Smart Citation
“…A x-amino-functionalized PS macroinitiator (M n = 2100, M w / M n = 1.15) was synthesized by atom transfer radical polymerization of styrene followed by Gabriel method as described in a previous paper [27]. A mixture of N-carboxy-c-benzyl-L-glutamate anhydride (3.00 g, 11.4 mmol), the PS macroinitiator (200 mg, 0.09 mmol), and dry chloroform (150 ml) was placed in a flask and stirred for 3 days.…”
Section: Synthesis Of Ps-b-poly(l-glu)mentioning
confidence: 99%
“…1. A PS-b-PBLG prepolymer was prepared as described in our previous paper [27]. Molecular weights of the PS and PBLG blocks were determined as M n = 2000 and 40,000 (the number of repeating units = 19 and 180), respectively.…”
Section: Synthesis and Characterization Of A Ps-b-poly(l-glu)mentioning
confidence: 99%
“…An additional work towards the effect of organic acid concentration (i.e., trifluoroacetic acid (TFA) in chloroform) on the conformational stability of hybrid block copolymers based on poly(γ-benzyl-Lglutamate) (PBLG) with polystyrene (PS) attached to the N or C terminus was recently performed [77]. Although the helix-coil transformation of PBLG is a well-investigated subject, it was found that deformation of the helical structure at the C-terminal side was predominantly caused by PS attachment instead of the TFA concentration, whereas the effect of TFA addition on the helical structure was greater on the N-terminal side.…”
Section: Supramolecular Organization Of Peptide-synthetic Polymer Hybmentioning
confidence: 99%
“…In fact, these secondary structures are the consequences of the intermolecular or intramolecular hydrogen bond interactions, and thus the conformations of PBLG would be affected by the environmental milieus. It has been reported that the solution polarity strongly influences the helix structures of PBLG [6], and that PBLG showed a helix-coil transformation in different solvents in the presence of an acid, such as trifluoroacetic acid [7][8][9]. Notably, the polymers blended with PBLG have the ability to influence the secondary conformations of PBLG, through either hydrogen bonds or π-π stacking interactions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As we have illustrated previously, the amphiphilic phenolic TPGS and the encapsulated Dox definitely have a predominant impact on both the secondary structures and the crystalline alignment of PBLG within the micellar system. In addition, the terminus of PBLG has a lack of intrahelical hydrogen bonds [8] and is physically incorporated inside the micellar system, thus the response of PBLG toward external pH environments and the releasing profiles needs to be comprehensively investigated. Here, the intracellular drug-releasing and the cytotoxicity toward human cancer cells will also be studied to evaluate the feasibility of these mixed micelles as a novel pH-responsive drug delivery system.…”
Section: Introductionmentioning
confidence: 99%